A randomised controlled trial of cognitive-behavioural therapy for women with problematic menopausal hot flushes: MENOS 2 trial protocol - Beverley Ayers; Eleanor Mann; Myra S Hunter (BMJ Open)
Objectives Hot flushes and night sweats (HF/NS) are experienced by 60–70% of menopausal women and are problematic for approximately 20–25%. Potential health risks associated with hormone-replacement therapy (HT) have led to a significant decline in HT use. There is therefore a need for safe, effective and evidence-based alternative treatments for menopausal symptoms. Previous exploratory work suggests that cognitive–behavioural therapy (CBT) is acceptable and effective for women with HF/NS during natural menopause and following breast-cancer treatment. This randomised controlled trial compares the effectiveness of Group CBT and Guided Self-Help CBT with no treatment control in reducing HF/NS Problem Rating and Frequency at post-treatment (main outcome) and at 6 months postrandomisation.Methods and analysis 120 women, with 10 or more HF/NS a week for a month, are recruited from GP surgeries and the local community of South London. They are randomised to either 4 weeks of Group CBT, 4 weeks guided Self-Help CBT or no treatment control. Participants attend a clinical interview, and complete baseline questionnaire measures of HF/NS Problem Rating and Frequency (primary outcomes), mood, quality of life, self-esteem, hot-flush beliefs and behaviours, optimism and somatic amplification, and undergo 24 h sternal skin conductance monitoring (SCC—physiological measure of HF/NS) (secondary outcomes). Post-treatment measures (SSC, questionnaires and use of medical services) are collected 6–8 weeks later and follow-up measures (questionnaires and a use of medical services measure) at 6 months postrandomisation.Ethics and dissemination Ethical registration was granted by King's College London Research Ethics Committee (ref: PNM/08/09-42). All participants provide written informed consent. If treatment is successful, a Group CBT training manual and training sessions for health professionals, and a Self-Help CBT book will be published. Other CBT delivery options will also be examined (including Computerised Self-Help CBT and Group CBT workshops).Clinical Trial Registration Number ISRCTN57302613.